To compare the functions \( f(x) = x^3 + 1 \) and \( g(x) = x + 1 \) and examine their intercepts, we need to find the x-intercepts and y-intercepts of both functions.
Finding Intercepts
-
Y-Intercepts:
- The y-intercept occurs when \( x = 0 \):
- For \( f(x) \): \[ f(0) = 0^3 + 1 = 1 \quad \text{(y-intercept is (0, 1))} \]
- For \( g(x) \): \[ g(0) = 0 + 1 = 1 \quad \text{(y-intercept is (0, 1))} \]
- The y-intercept occurs when \( x = 0 \):
-
X-Intercepts:
- The x-intercept occurs when \( y = 0 \) (i.e., set the functions to 0 and solve for \( x \)):
- For \( f(x) \): \[ x^3 + 1 = 0 \implies x^3 = -1 \implies x = -1 \quad \text{(x-intercept is (-1, 0))} \]
- For \( g(x) \): \[ x + 1 = 0 \implies x = -1 \quad \text{(x-intercept is (-1, 0))} \]
- The x-intercept occurs when \( y = 0 \) (i.e., set the functions to 0 and solve for \( x \)):
Summary of Intercepts
- Both functions have:
- An x-intercept of (-1, 0)
- A y-intercept of (0, 1)
Comparing with Statements
Now let's compare what we found with the statements provided:
- Both functions have an x-intercept of (-1,0) and a y-intercept of (0, 1). (True)
- The graphs intersect at (1, 2). (We need to check this point, but first, we can see it's not a statement regarding intercepts.)
- Both functions have a y-intercept of (-1,0) and an x-intercept of (0, 1). (False, as shown above.)
- The x- and y-intercepts are different for each function. (False, as shown above.)
Conclusion
The statement that is true about the intercepts of the functions is:
Both functions have an x-intercept of (-1,0) and a y-intercept of (0, 1).